The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1088/0256-307x/31/7/078101
|View full text |Cite
|
Sign up to set email alerts
|

Resistive Switching Behavior in Amorphous Aluminum Oxide Film Grown by Chemical Vapor Deposition

Abstract: The repeatable bipolar resistive switching phenomenon is observed in amorphous Al2O3 prepared by metalorganic chemical vapor deposition on ITO glass, with ITO as the bottom electrode and Ag as the top electrode. The crystal structure, morphology, composition and optical properties of Al2O3 thin films are investigated by x-ray diffraction, x-ray photoelectron spectroscopy, atomic force microscopy and ultraviolet-visible-infrared spectroscopy, respectively. The electronic character of Ag/Al2O3/ITO structure is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Metal-oxide-based resistive random-access memories (RRAMs) [ 17 , 18 ] are promising nonvolatile memories [ 19 , 20 , 21 ]. Various binary oxides, such as Al 2 O 3 [ 22 , 23 ], HfO 2 [ 24 , 25 , 26 ], ZrO 2 [ 27 , 28 , 29 ], Ta 2 O 5 [ 30 , 31 ], and ZnO [ 32 , 33 ], have been studied for resistive-switching (RS)-memory devices owing to their relatively simple structure and ease of fabrication. Additionally, multicomponent perovskite oxides, such as Pr 0.3 Ca 0.7 MnO 3 [ 34 , 35 , 36 ], have been widely examined for their nonvolatile, forming-free memory switching; area scalability; low variability; and good reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Metal-oxide-based resistive random-access memories (RRAMs) [ 17 , 18 ] are promising nonvolatile memories [ 19 , 20 , 21 ]. Various binary oxides, such as Al 2 O 3 [ 22 , 23 ], HfO 2 [ 24 , 25 , 26 ], ZrO 2 [ 27 , 28 , 29 ], Ta 2 O 5 [ 30 , 31 ], and ZnO [ 32 , 33 ], have been studied for resistive-switching (RS)-memory devices owing to their relatively simple structure and ease of fabrication. Additionally, multicomponent perovskite oxides, such as Pr 0.3 Ca 0.7 MnO 3 [ 34 , 35 , 36 ], have been widely examined for their nonvolatile, forming-free memory switching; area scalability; low variability; and good reliability.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the device could be fabricated in a simple metal-insulator-metal (MIM) [3] structure, enabling the high-density cell structure of a cross-bar array with 4F 2 [4,5]. It was reported that numerous transition metal oxides, including Al 2 O 3 [6,7], HfO 2 [8][9][10], NiO x [11][12][13][14], TiO x [15,16], TaO x [17,18], Nb 2 O 5 [19,20], and Pr 1−x Ca x MnO 3 [21][22][23] show resistive switching (RS) characteristics. Moreover, various deposition techniques, such as sputtering [24][25][26][27][28], atomic layer deposition (ALD) [29] and pulsed laser deposition (PLD) [30] were used for the formation of such oxides.…”
Section: Introductionmentioning
confidence: 99%
“…This development has attracted widespread attention in the industry and academia, and many new investigations of resistive memory have been initiated by researchers [13,14]. The RS effect of the insulator layer has been discovered in various kinds of amorphous metal oxides, such as ZnO, HfO 2 , TiO 2 , MgO, Al 2 O 3 , and Y 2 O 3 [15][16][17][18][19]; and in amorphous perovskite and layered perovskite oxides such as YCrO 3 , Pr 0.67 Sr 0.33 MnO 3 , Bi 3.15 Bd 0.85 Ti 3 O 12 , SrTiO 3 and Nb-doped SrTiO 3 [20][21][22][23][24][25][26], etc. Among these, the amorphous strontium titanate-based memory structure uses the following electrodes: Pt, Ti, and indium tin oxide (ITO) [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%